KONSTRUKSI MAKNA PERKAWINAN DI USIA DINI (STUDI FENOMENOLOGI PADA PEREMPUAN PELAKU PERKAWINAN USIA DINI DI KECAMATAN TAPUNG HULU) - Tri Suci Ramadhani; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
An early marriage has long been a problem that is fairly complex because it involves aspects of economics, education, and socio-cultural communities in an area. In Sub Tapung Hulu early marriage seemed to be a common thing to do. Lack of reasoning and knowledge on family life makes young female taking premature decisions which in this case is the early marriage. This research aims to determine the motive, the meaning and the communication experience of female in marriage to undergo an early age in the Tapung Hulu District.The research is a qualitative research with phenomenology approach. Informant of this research are the female offenders early marriage in Tapung Hulu Districtwith five persons were selected using snowball technique and based on predetermined criteria. The data was collected through interviews, observation and documentation. The data analysis techniques includes data reduction, data presentation and conclusion and verification.The results of this research shows that first, the motives of female did this early marriage in Tapung Hulu District consist of because motive which has conducted biological relationships and unwed, poor education and a sense of comfort and trust to the couple. While in order to motive is to live happily in this world and in the hereafter, to ease the economic burden of the family and want to live independently. Second, meaningness that given by actors early marriage to marriage among others, as a consequence of the actions of the past, of sacrifices in their youth and as the most logical choice to be taken. Third, the communication experience as much fun as the support of family and relatives, a sense of comfort and be acknowledged by the couple and interaction and feel helped by a neighbor when adversity struck. Meanwhile, the communication experience not as enjoyable as a byword in the neighborhood, the more succumb if there is debate and disagreement with a spouse, parent disappointment against the perpetrators of early marriage are already pregnant out of wedlock, and got ridicule from peers.Keywords : Early Marriage, Phenomenology, and, Female